Photo-crosslinking injectable Photothermal antibacterial hydrogel based on quaternary ammonium grafted chitosan and hyaluronic acid for infected wound healing - Xinbo Ma; Aoao Wang; Xuelian Zhang; Juan Zhang; Jiawei Li; Xi Fu; Peng Wang; Yantao Zhao; Xiaonan Huang (Materials Today Bio)
Antibacterial hydrogels not only provide a better environment for skin wounds to avoid infection but also accelerate wound healing. Herein, chitosan modified by a quaternary ammonium salt (CQ), and hyaluronic acid grafted with methacrylate (HM) were designed and synthesized to prepare an injectable photo-crosslinking hydrogel for wound dressing with inherent antibacterial and photothermal properties. CQ and HM exhibited excellent biocompatibility, improved water retention, and antibacterial activity, illustrating vast potential as an antibacterial material in various applications. MXene, a type of 2D nanomaterial, has been widely researched due to its photothermal properties. The CQ and HM polymer precursor could be mixed with Mxene and then crosslinked with 395 nm UV radiation under mild conditions to form a 3D network structure CQ-HM/MXene hydrogel. This hydrogel displayed an appropriate swelling ratio, elastic modulus, photothermal property and excellent biocompatibility. The injectable property of the hydrogel allowed it to easily cover the wound. In vitro and in vivo studies showed that the injectable hydrogel had low cytotoxicity and excellent antibacterial properties, which could help promote wound healing. In summary, this novel CQ-HA/MXene hydrogel has the potential for application in skin wound healing due to inherent antibacterial activity and photothermal effect.